1985
DOI: 10.1161/01.res.56.6.816
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a kininogenase from rat vascular tissue resembling tissue kallikrein.

Abstract: A kininogenase resembling glandular kallikrein was partially purified from vascular tissue and characterized. Saline-perfused rat tail arteries and veins were homogenized in 0.25 M sucrose containing 10 mM Tris-HCl (pH 7.4). The homogenate was centrifuged at 105,000 g for 60 minutes, and a vascular kininogenase was purified from the supernatant by chromatofocusing, affinity chromatography on immobilized antibodies against rat urinary kallikrein, and gel filtration on Sephadex G-100. The inhibitory effects of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
51
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(53 citation statements)
references
References 11 publications
2
51
0
Order By: Relevance
“…The vascular kininogenase is inhibited by aprotinin and phenylmethylsulfonyl fluoride (PMSF) but is resistant to SBTI, 4 which is characteristic of glandular kallikrein. 5 SBTI was included in the incubation buffer to inhibit plasma kallikrein and trypsin-like enzymes that could contaminate the homogenates.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The vascular kininogenase is inhibited by aprotinin and phenylmethylsulfonyl fluoride (PMSF) but is resistant to SBTI, 4 which is characteristic of glandular kallikrein. 5 SBTI was included in the incubation buffer to inhibit plasma kallikrein and trypsin-like enzymes that could contaminate the homogenates.…”
Section: Methodsmentioning
confidence: 99%
“…It was inhibited by aprotinin and by polyclonal and monoclonal antibodies against glandular kallikrein and was resistant to soybean trypsin inhibitor (SBTI). 4 Although the function of this vascular kininogenase is not known, it could participate in circulatory homeostasis through local generation of kinins. The present study was designed to determine whether one-kidney, one clip renovascular hypertension alters the concentration of vascular kininogenase.…”
mentioning
confidence: 99%
“…While the kallikrein gene is expressed mainly in the submandibular gland, pancreas and kidney, we detected small amounts of kallikrein mRNA in the heart, vascular tissue, and adrenal glands on polymerase chain reaction (PCR) (189,237). Kallikrein and similar enzymes have been found in the arteries and veins (190), heart (188), brain (58), spleen (57), adrenal glands (255), and blood cells (189); they have also been observed in the pituitary gland (66,216), pancreas (84), large and small intestines (242,320), and salivary and sweat glands (106) along with their exocrine secretions. Some of these enzymes were probably true kallikrein, while others may represent separate members of the kallikrein family.…”
Section: Introductionmentioning
confidence: 86%
“…The kallikrein-kinin system in the vasculature and regulation of local blood flow-Arteries and veins contain a kallikrein-like enzyme, and both vascular tissue and smooth muscle cells in culture contain kallikrein mRNA (190,237). Vascular smooth muscle cells in culture release both kallikrein and kininogen (200).…”
Section: The Kallikrein-kinin System In Inflammationmentioning
confidence: 99%
“…78 We do not know which enzymes release tissue kinins. We have reported that vascular tissue contains a kininogenase that has the same properties as glandular kallikrein 9 and that messenger RNA for kallikrein is present in vascular tissue and smooth muscle cells in culture. 10 Oza et al n reported that vascular smooth muscle cells in culture release both kallikrein and kininogen (kallikrein substrate).…”
mentioning
confidence: 99%